Software Development for First Aid Decision Support System - Ahmed, Ahmed Shihab; Salah, Hussein Ali; Jameel, Jalal Q. (Iraqi Journal of Science, 2020)
This work presents an approach to deal with modelling a decision support system framework to introduce an application for decisions in medical knowledge system analysis. First aid is extremely important worldwide and, hence, a decision support framework, know as First Aid Decision Support System (FADSS), was designed and implemented to access experimental cases exerting danger to the general population, offering advanced conditions for testing abilities in research and arranging an emergency treatment through the graphical user interface (UI). The design of first aid treatment in FADSS depends on the general cases in first aid. We presented a strategy to manage first aid treatment by modelling an application (FADSS) that assists people in finding information about first aid cases that are available as an application service. FADSS service uses a set of 15 important situations that might happen to people. The decision for treatment is suggested on the system for a different accident. FADSS tests the information in real-time by using mathematical models, decision tree and data mining (C4.5 algorithm) that are used in this research to build a decision making system. The system automatically sends warnings when the case is very critical, using text messages as email reports. The main objective of this study is to provide an efficient tool that helps people and junior workers in first aid centres in order to find the available resources of information.